Domesticity and family: ambiguity and contradiction in the models of femininity under Franco's regime - Eider de Dios Fernández (Feminismo/s, 2014)
The establishment of Franco’s dictatorship meant the consolidation of a family model which combined catholic and ‘falangista’ elements and legitimized the new regime. The role played by women in the family/familial structure was very important, despite the subordinate role women played in society; influence and not power was the area reserved for them. The main objective of this paper is a consideration of the way in which these women interiorised, and had to deal with, the gender postulates of the regime. The use of the oral source, always rich in nuance, will lead us in the process of subjective understanding of four women belonging to different social classes who learnt to be women as daughters, girlfriends, wives and mothers under Francoism.